Diagonally implicit block backward differentiation formulas for solving ordinary differential equations - Mohd Zawawi, Iskandar Shah; Ibrahim, Zarina Bibi; Ismail, Fudziah; Abdul Majid, Zanariah (Hindawi Publishing Corporation, 2012)
This paper focuses on the derivation of diagonally implicit two-point block backward differentiation formulas (DI2BBDF) for solving first-order initial value problem (IVP) with two fixed points. The method approximates the solution at two points simultaneously. The implementation and the stability of the proposed method are also discussed. A performance of the DI2BBDF is compared with the existing methods.